1977
DOI: 10.1161/01.cir.55.6.839
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular and coronary angiographic anatomy. Relationship to ventricular irritability in the late hospital phase of acute myocardial infarction.

Abstract: Late hospital phase ventricular arrhythmias in acute myocardial infarction (MI) have been associated with a high incidence of sudden death following hospital discharge. Thirty-eight patients were studied 10-24 days following onset of symptoms of MI. Each patient had a 24-hour ambulatory ECG tape recording and left ventricular and coronary angiography performed. Patients with complicated ventricular arrhythmias (multiform, coupled, R on T VPCs or ventricular tachycardia), when compared to those with uncomplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…22 We did not find a similar relationship between the extent of cor-VOL 60, No 6, DECEMBER 1979 onary disease and arrhythmias in patients with VAP. However, the presence of arrhythmias correlates with the severity of ischemia measured by ST-segment elevation and AR during episodes of VAP.…”
Section: Discussionmentioning
confidence: 57%
“…22 We did not find a similar relationship between the extent of cor-VOL 60, No 6, DECEMBER 1979 onary disease and arrhythmias in patients with VAP. However, the presence of arrhythmias correlates with the severity of ischemia measured by ST-segment elevation and AR during episodes of VAP.…”
Section: Discussionmentioning
confidence: 57%
“…'6 Multigated Blood Pool Imaging After the delayed 201T images were obtained, equilibrium-gated blood pool imaging was performed at rest to determine left ventricular ejection fraction and segmental wall motion patterns. Patients were injected with unlabeled stannous pyrophosphate (Mallinckrodt, Inc.), followed 30 minutes later by 20 patients, the inferior and inferoapical segments were considered. Also, in four patients (two from each group), the mid-high posterolateral wall was designated an infarct-related segment because angiography revealed that the circumflex artery was the infarct vessel.…”
Section: Exercise Myocardial Scintigraphymentioning
confidence: 99%
“…For example, if R on T is present, grade 5 is assigned regardless of ventricular extrasystoles frequency or other complex features. The three frequency categories (0, > 0 but <30, >30 ventricular extrasystoles per hour) and 717 BHJ389/80 Table 1 The Lown grading system for ventricular arrhythmias Lown grade Definition 0 No ventricular premature depolarisations 1 Less than 30 ventricular extrasystoles per hour 2 30 or more ventricular extrasystoles per hour 3 Multiform ventricular extrasystoles 4A Two consecutive ventricular extrasystoles 4B…”
mentioning
confidence: 99%